2022
DOI: 10.1007/s13201-022-01724-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic supported activated carbon obtained from walnut shells for bisphenol-a uptake from aqueous solution

Abstract: This work investigated the usability of activated carbon walnut shell (ACWS) and magnetic activated carbon walnut shell (MACWS) for Bisphenol-A (BPA) elimination from aqueous solution. Fourier-transform infrared (FT-IR) and X-ray diffraction (XRD) were used to study the chemistry of the adsorbents. Batch sorption studies at different temperatures, contact time, adsorbent dosage, pH and varied Bisphenol-A concentrations were performed, while pseudo-first-order and pseudo-second-order kinetics models were deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Activated carbons prepared from argan nut shell by phosphoric acid also show great potential in BPA adsorption(93%)(Zbair et al 2018). As demonstrated byUzosike et al, they found the adsorption capacity of BPA on activated carbon derived from walnut shell and magnetic activated carbon derived from a walnut shell were 115.85 mg/g and 166.67 mg/g, respectively(Uzosike et al 2022). Likewise, in a study byWang and Zhang et al, magnetic biochar was prepared with excellent reusability (Wang and Zhang 2020).…”
mentioning
confidence: 88%
“…Activated carbons prepared from argan nut shell by phosphoric acid also show great potential in BPA adsorption(93%)(Zbair et al 2018). As demonstrated byUzosike et al, they found the adsorption capacity of BPA on activated carbon derived from walnut shell and magnetic activated carbon derived from a walnut shell were 115.85 mg/g and 166.67 mg/g, respectively(Uzosike et al 2022). Likewise, in a study byWang and Zhang et al, magnetic biochar was prepared with excellent reusability (Wang and Zhang 2020).…”
mentioning
confidence: 88%
“…Effluents discharged from industry into the aquatic environment are among the chief causes of the deterioration of water quality 1 4 . Rapid increase in industrialization leading to urbanization had led to the released of huge quantities of wastewater into the environment, causing pollution 5 , 6 . The textile industry as well as its dye-containing wastewaters is the major sources of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The textile industry as well as its dye-containing wastewaters is the major sources of organic pollutants. Report has it that up to 25% of textile dyes during dyeing process is lost, while about 2–20% is released into the environmental as aqueous effluents 6 , 7 . Discharge of effluents containing dyes into water body is detrimental due to their colours which prevent the flow of oxygen directly into water 3 – 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations